Aid and the political economy of policy change - Killick, Tony (Routledge, 1998)
This volume looks at the effectiveness of conditionality in structural adjustment programmes. Tony Killick charts the emergence of conditionality, and challenges the widely held assumption that it is a cooperative process.
Keywords: Economic assistance.; Structural adjustment (Economic policy); Economic history -- 1971-1990.; Economic history -- 1990-; Aide économique.; Ajustement structurel (Économie); Histoire économique -- 1971-1990.; Histoire économique -- 1990-; assistance.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Economic assistance; Economic history; Since 1971